2008
DOI: 10.1302/0301-620x.90b12.21378
|View full text |Cite
|
Sign up to set email alerts
|

Medial transport of the fibula using the Ilizarov device for reconstruction of a massive defect of the tibia in two children

Abstract: We present two children with massive defects of the tibia and an associated active infection who were treated by medial transport of the fibula using the Ilizarov device. The first child had chronic discharging osteomyelitis which affected the whole tibial shaft. The second had sustained bilateral grade-IIIB open tibial fractures in a motor-car accident. The first child was followed up for three years and the second for two years. Both achieved solid union between the proximal and distal stumps of the tibia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…To date, the reported series of fibula tibilisation, though not large, have been encouraging for avoiding amputation [6,11,[22][23][24]. Ours is the largest historical series of patients, and demonstrates that the technique can be carefully carried out at a specific transporting rate thus reducing the incidence of peroneal neuropathy or paresis which could happen by acute fibula transfer in the conditions of scarred soft tissue.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…To date, the reported series of fibula tibilisation, though not large, have been encouraging for avoiding amputation [6,11,[22][23][24]. Ours is the largest historical series of patients, and demonstrates that the technique can be carefully carried out at a specific transporting rate thus reducing the incidence of peroneal neuropathy or paresis which could happen by acute fibula transfer in the conditions of scarred soft tissue.…”
Section: Discussionmentioning
confidence: 80%
“…The fibula seems to be a good biological graft when used for the Ilizarov tibiofibular synostosis that is less traumatic and costly as there is no need to intervene on the contralateral segment. Gradual transport of the fibular fragment does not affect the nutrient vessels and results in regeneration and consolidation [6,11,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…The method of a vascularised fibular transfer may be excluded by infection or major soft tissue defects [19], and a considerable dissection of soft tissues and a satisfactory vascular anastomosis are required for the technique, so the treatment requires an experienced microsurgical team, and it is a demanding technique [20]. Tibio-fibular synopsis seeks to achieve a secure synostosis of the tibia and fibula in its eccentric position, this leads to asymmetrical loading through the fibula, which may be the failure reason for the treatment of massive tibial bone defects [9,21]. Ilizarov bone transport is a versatile method, it can be used to reconstruct bone defect and correct deformity simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Large segmental defects of the tibia are challenging therapeutic problems (1,2,4,5,11,13). They can be caused by severe trauma, osteomyelitis, tumor resection, reconstruction or congenital etiologies such as agenesis or pseudoarthrosis of the tibia.…”
Section: Discussionmentioning
confidence: 99%
“…The reported time for hypertrophy of the fibula varies from one to two years or from two to four years; however, Tuli et al stated that no significant change in the diameter of the fibula is observed after five years (6,17). Fracture of tibialized fibula was not reported in most studies of fibular centralization with different techniques (3,5,6,(9)(10)(11). Keeting et al reported one stress fracture of the fibula in 16 cases of fibular transfer that were treated with sufficient immobilization time.…”
Section: Discussionmentioning
confidence: 99%